Realistic challenges and path options for the high-quality development of smart stadiums in China - Shaoquan Chu (Quality in Sport)
The high-quality development of smart stadiums has become a key concern for the industry and academia. This study uses literature, fieldwork methods and logical analysis to sort out the reality of the development of intelligent stadiums in China and make corresponding recommendations. The study finds that the problems of high-quality construction of smart stadiums in China include: information technology treats the masses as a tame object and a test object for the safety valve, there is a paradox between algorithmic "de-deviation" and "personalised" sports services, and there is a lack of product standards and construction standards for smart stadium facilities. The following recommendations were made: strengthen the functional construction of venues to promote the "penetration" of sports lifestyle awareness; strengthen the low-carbon construction of venues to improve sustainable development; and implement the new concept of "two developments" to promote the high-quality development of venues.